Nurses’ Knowledge Regarding Management of Hypovolemic Shock: A Cross-Sectional Study: Pengetahuan Perawat Mengenai Manajemen Syok Hipovolemik: Sebuah Studi Cross-Sectional - Maher Atiyah (Academia Open, 2024)
Hypovolemic shock, a common post-surgery complication, poses significant challenges globally, particularly in trauma-related fatalities. Understanding nurses' knowledge of hypovolemic shock management is crucial for improving patient care and reducing mortality rates. However, research assessing nurses' knowledge in this area remains limited, especially in specific hospital settings. This cross-sectional study aimed to evaluate nurses' knowledge of hypovolemic shock management at Al-Basrah Teaching Hospitals. Data from 120 nurses were collected using a questionnaire-based survey and analyzed using SPSS version 26. Results indicated that most nurses demonstrated good knowledge (58%), while 39% had moderate knowledge and 3% had inadequate knowledge. This study highlights the need for targeted educational interventions to enhance nurses' understanding of hypovolemic shock management, potentially leading to improved patient outcomes and reduced mortality rates. Highlight: Comprehensive assessment: Nurses' knowledge evaluated at Al-Basrah Teaching Hospitals. Knowledge distribution: Majority of nurses showed good understanding of shock management. Practice implications: Highlight importance of targeted educational interventions for nurses. Keywoard: Hypovolemic Shock, Nurses' Knowledge, Management, Al-Basrah Teaching Hospitals, Patient Care